Entomopathogenic nematodes : characterization of a new species, long–term storage and control of obscure mealybug, Pseudococcus viburni (Hemiptera: Pseudococcidae) under laboratory conditions - Stokwe, Nomakholwa Faith (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MScAgric (Conservation Ecology and Entomology)--University of Stellenbosch, 2009.